2012
DOI: 10.1107/s0909049512039118
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for low-frequency synchrotron X-ray beam position fluctuations for dynamic visualizations

Abstract: Synchrotron X-ray radiography on beamline 05B1-1 at the Canadian Light Source Inc. was employed to study dynamic liquid water transport in the porous electrode materials of polymer electrolyte membrane fuel cells. Dynamic liquid water distributions were quantified for each radiograph in a sequence, and non-physical liquid water measurements were obtained. It was determined that the position of the beam oscillated vertically with an amplitude of ~25 µm at the sample and a frequency of ~50 mHz. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 14 publications
0
54
0
Order By: Relevance
“…Half of the active area (at the centre) was analyzed where the beam intensity distribution provided the highest quality of image capture. 21 As discussed in the reference, 21 the distribution of X-ray beam intensity across the imaging region was non-uniform. The intensity of the beam was highest at the central region and decreased away from this region.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Half of the active area (at the centre) was analyzed where the beam intensity distribution provided the highest quality of image capture. 21 As discussed in the reference, 21 the distribution of X-ray beam intensity across the imaging region was non-uniform. The intensity of the beam was highest at the central region and decreased away from this region.…”
Section: Methodsmentioning
confidence: 99%
“…14,20,21 The outlets of the channels were diverted away from the beam path in a "Y" configuration ( Figure 2) in order to minimize the liquid water accumulation in the corner regions of the channels. By diverting the outlets, the beam intensity across the ribs of the flow field was evenly distributed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though X-ray photons are not as sensitive as a neutron beam to the presence of liquid water, Chevalier et al [29] demonstrated that synchrotron X-ray radiography can achieve similar accuracy to neutron radiography with a high level of precision. Recent works have improved the accuracy and reliability of this technique for PEM fuel cell visualizations by establishing methodologies for correcting beam position movement artifacts [58], calibrating the attenuation coefficient of liquid water and correcting sample movement artifacts [44], and considering photon scattering and harmonics [59]. In addition, the fast temporal resolutions possible with synchrotron X-ray radiography allow for dynamic visualizations of transient liquid water behaviour [60,61] and enable high-resolution in-situ tomography to resolve liquid water saturation in 3-D [48,52,62].…”
Section: Visualizations Of Liquid Water Saturationmentioning
confidence: 99%